Conclusions and recommendations stemming from research conducted by IRWiR PAN in 2012 - Zawalińska, Katarzyna (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2013)
Conclusions and recommendations stemming from research conducted by IRWiR PAN in 2012.